Housing Affordability Among Generation Y - Mohd. Raslim, Faraziera; Lu Ping, Chong; Jaafar, Mastura; Sakina Mokhtar Azizi, Nurul (International Journal of Engineering and Technology, 2018)
The Affordable housing is a prerequisite element to showcase a country is well-developed in terms of social economy growth and social welfare. While in the view of affordability, it is not a characteristic of housing â€“ it is a relationship between and people. In fact, housing affordability issues happened in every world cities of the planet but no one envisages it properly especially when this issues fall upon on young generation, so-called Generation Y. Generally, this generation is the descendant of Baby Boomers/ Generation X, who born between the years 1979 and 1994. Gen Y is a cohort made up of about 60 million individuals and now make 44% of the population in Malaysia. The Malaysia government has introduced several housing schemes especially for those new workforces in nationwide to ensure every of them are able to afford a home. Those housing schemes are included Housing Loan Scheme, My First Home Scheme, Perumahan Rakyat 1 Malaysia (PRIMA), Rumah Idaman Rakyat, My Home Scheme and Youth Housing Scheme (YHS) which are beneficial to the first-homebuyers. Despite the efforts by Malaysian government, housing affordability still remains an issue among Malaysian Generation Y. Thus, this questionnaire survey have been distributed to Generation Y in order to investigate the effectiveness of the government initiatives to assist Gen Y in homeownership. It is hoped that this study will contribute to the knowledge and understanding on housing affordability level for the young generation to further improve Malaysia housing scheme and boost up the housing market.Â Â